Avaliação fitoquímica e farmacológica da própolis da abelha frieseomelitta doederleini produzida no semi-árido nordestino - Nunes, Francisco Vitor Aires (Universidade Federal Rural do Semi-Árido, 2018)
Propolis is a resinous material of coloration and consistency varied, gotten for bees through the resin collection of the flora of the region, and modified for the enzyme action contained in its saliva. The propolis produced by the bees with sting already widely had been studied in order to prove its pharmacological activities and are thus, used for diverse medicinal applications. However, related to the propolis of the bee Frieseomelitta doederleini, studies systemize on its pharmacological activities are scarce. This study objectified to evaluate the phytochemistry composition and the pharmacological activities of the propolis of bee F. doederleini; therefore, samples of bee propolis had been extracted in the city of Serra do Mel, West Region of the Rio Grande do Norte, which were evaluated pharmacological activities: antioxidant (through method DPPH-2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2'-azino-bis (3-ethylbenzothiazolin) 6-sulfonic acid); antibacterial through the method of diffusion in agar and microdilution to determine Minimum the Inhibitory Concentration (CIM) and Minimum Bacterial Concentration (CBM); healing, through the induction of experimental surgical wounds in Wistar rats, beyond the growth of fibroblasts in real time; cytotoxic for the method of the MTT (bromide of [3- (4,5-dimetiltiazol-2-il) - 2,5- diphenyltetrazolium) and finally, the mutagenicity for the method of micronuclei. The phytochemistry analysis disclosed the presence of saponins, phenolic composites, flavonoids aglycones and the method of Co-CCD identified to the composites quercetin and kaferol. The propolis presented concentration of 35,55mg EAG.g-1 of total phenols. It presented expressive antioxidant activity for method DPPH, with a 46,39 ppm of IC50, already for method ABTS the antioxidant activity was discreet, with a IC50 440.44 ppm. The extract was considered efficient with respect to antibacterial activity, therefore ≥ 9 mm for all promoted the halos formation of inhibition with size strains when tested in agar Mueller Hinton. Minimum the Inhibitory Concentration (CIM), in the microdilution test, varied of 3,125 25mg.mL-1 for the 11 microorganism tested, showing best the CIM against aeruginosa Pseudomonas, Gram-negative bacterium related the resistance to antimicrobials. The Minimum Bacterial Concentration (CBM) varied of 6,25 the 50 mg.mL-1. The analysis of the process of healing under the clinical, macroscopic and histological points of view allowed to conclude, that the use of the cream to the base of propolis presented positive influence in the healing of experimental cutaneous wounds, for promoting less intense reaction inflammatory and faster closing of the wounds in relation to the group has controlled, as well as stimulated the biggest growth of fibroblasts. In the test of cytotoxicity by MTT it is possible to observe higher cytotoxic activity for colon carcinoma cells at concentrations of 3,12 μg.mL-1, 6,25 μg.mL-1 e 12,5 μg.mL-1, this finishes concentration obtained to more than inhibit the cellular viability of the carcinogenic cells in 50%. How much the evaluation of the mutagenic potential the propolis induced increase in the frequency of micronucleate cells only in the biggest evaluated concentration (250 μg.mL-1). Thus it was possible to conclude that the hydroalcoholic stratum of the propolis of the bee Frieseomelitta doederleini presented a chemical composition varied and promising pharmacological activities, being distinguished antirust, antioxidant, healing and anti-neoplasm
Keywords: Composição fitoquímica; Própolis; Frieseomelitta doederleini; Atividade farmacológica; Phytochemical composition; Propolis; Frieseomelitta doederleini; Pharmacological activity; CIENCIAS AGRARIAS::MEDICINA VETERINARIA